Konstruksi Makna dan Realitas Sosial dalam Perspektif Interaksionisme Simbolik dan Postmodernisme - Rezky Tania; Susan Febriyanti; Rozalia Rozalia; Andita Novaliana; Ayu Nur Safitri; Aftesia Labira Lauli; Febra Anjar Kusuma; Dian Permata Sari; Karyadi Hidayat (Indo Publishing, 2026)
The construction of meaning and social reality is a process in which individuals and groups actively construct an understanding of the social world through interactions and symbols. From a symbolic interactionist perspective, meaning is understood as the result of individual interpretations formed through social interactions using symbols such as language, gestures, and actions. Meanwhile, from a postmodernist perspective, social reality is understood as something that is not singular and objective, but relative, variable, and influenced by media and technological advances. This study aims to analyze the construction of meaning and social reality by combining these two perspectives in the context of modern life. The method used is a qualitative approach with a descriptive-analytical type through a literature review of various related scientific sources. The results show that meaning and social reality are formed through social interactions and are also influenced by digital media, which expands and accelerates the construction process. Social media plays a significant role in shaping identities, perceptions, and social realities, such as beauty standards, concepts of success, and ideal lifestyles. Therefore, a critical attitude and media literacy are needed so that individuals can understand and filter the reality constructed in social life.